2. POTENSI ANCAMAN ASEAN OPEN SKY POLICY 2015 TERHADAP KEAMANAN NASIONAL INDONESIA - Setiyanti, Dina; Putranti, Ika Riswanti; Rosyidin, Mohammad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The ASEAN Open Sky has begin since March 2015, but the AOSP beside openopportunity for Indonesia, also provides challenges and threats in Indonesia flights,particularly in the field of security. Offense of the airspace of Indonesia often occur.Foreign aircraft often pass freely, while our aviation authorities can not do anything. Infact, there are national air space controlled by neighboring countries, and then they getbenefit from the use of the airline. The last few years, several cases of airspace violationsof Indonesia by commercial aircraft and foreign military has happened and with thepresence of AOSP 2015 increasingly opened up a gap for air violation.